Low‐molecular‐weight organic acids enhance desorption of polycyclic aromatic hydrocarbons from soil. (9th February 2015) - Ling, W.; Sun, R.; Gao, X.; Xu, R.; Li, H.
Summary The impact of low‐molecular‐weight organic acids (LMWOAs) on desorption of phenanthrene and pyrene as representative polycyclic aromatic hydrocarbons (PAHs) from a contaminated soil was investigated by using a laboratory batch experiment. Three LMWOAs were used in this study and were citric, oxalic and malic acids. The LMWOAs in aqueous solution promoted desorption of PAHs from soil significantly and demonstrated an increasing trend as the concentration of LMWOAs increased. When compared with desorption of phenanthrene and pyrene from soil to water, the addition of LMWOAs enhanced desorption of test PAHs by up to 285 and 299%, respectively. Among the three LMWOAs studied, citric acid demonstrated the greatest efficiency in promoting PAH desorption from soil. Solutions of LMWOA continuously promoted PAH removal from soil during the multiple cycles of desorption. Overall, the experimental results suggest that LMWOAs in aqueous solution could disrupt soil organic matter (SOM)–metal cation–mineral linkages in soils, resulting in the release of SOM from soil and simultaneous increase of dissolved organic carbon (DOC) in solution. The loss of SOM from soil and increase of DOC in solution are responsible for the enhanced PAH desorption from soil. The positive correlation between DOC in solution and desorbed PAHs from soil suggests that the loss of SOM from soil plays an important role in LMWOA‐enhanced desorption of PAHs from soil.